Comprehensive snow, soil, water, and climate data from Qeqertarsuaq (Disko Island), West Kalaallit Nunaat (Greenland), 2022-2025 - Boike, Julia; Bornemann, Niko; Cable, William L; Gottuk, Jannika; Hammar, Jennika; Kaiser, Soraya; Kutzbach, Lars; Mewes, Lars-Hendrik; Stuenzi, Simone Maria (PANGAEA, 2025)
Permafrost regions play a critical role in the global climate system, as they contain significant stores of organic carbon, much of which has been preserved in permanently frozen soil. Arctic regions are warming at a rate faster than the global average, leading to the thawing of permafrost. Understanding the control factors of CH4 fluxes, such as snow cover, soil moisture, temperature and chemical properties, in changing and heterogeneous permafrost landscapes is essential. Here we present a comprehensive data set collection from Kuup Ilua (Blæsedalen), Qeqertarsuaq (Disko Island), West Kalaallit Nunaat (Greenland). The collection includes results from soil, surface and pore water analyses, snow depth, penetration resistance in snow correlated to snow microstructure (density and specific surface area), distributed air, surface and soil temperatures and soil moisture collected along three uphill oriented transects on the eastern slope of Kuup Ilua. In addition, we present results from a soil and weather station that was installed in September 2023 at transect 3 (69.278, -53.476, elevation ~100 m a.s.l.) including air temperature and humidity, wind speed and direction, precipitation, solar radiation, snow depth, soil heat flux, soil moisture, soil temperature, snow conditions, and snow temperature. This data set collection is part of the MOMENT project (Permafrost Research Towards Integrated Observation and Modelling of the Methane Budget of Ecosystems). MOMENT is funded by the Federal Ministry of Research, Technology and Space (BMFTR) (former BMBF) and the data collection comprises three years of data.
Keywords: Arctic; Disko Island; GNSS; Greenland; Kalaallit Nunaat; Qeqertarsuaq; snow depth